2019
DOI: 10.1111/jam.14187
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interaction on dual‐species biofilm formation by spoilage bacteria, Shewanella baltica and Pseudomonas fluorescens

Abstract: Aims: This study aims to characterize the biofilm produced by mono-and dual-species of Shewanella baltica and Pseudomonas fluorescens as fish spoilers at the different incubation temperature, and to elucidate the interactive behaviour of dual-species biofilm development. Methods and Results: The mono-and dual-species biofilm formation and adhesion characteristics of S. baltica and P. fluorescens were evaluated by using crystal violet staining, scanning electron microscopy and confocal laser scanning microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Biofilms forming assay was carried out as described previously (Zhu et al, 2019) with slight modifications. The overnight broth cultures of S. putrefaciens WS13 were grown to approximately 8 log CFU mL −1 (OD 600 ≈0.8) and diluted with fresh sterile LB medium (1:100), then added 1 mL of dilution culture to 24-well polystyrene microtiter plates.…”
Section: Formation and Quantification Of Biofilmsmentioning
confidence: 99%
“…Biofilms forming assay was carried out as described previously (Zhu et al, 2019) with slight modifications. The overnight broth cultures of S. putrefaciens WS13 were grown to approximately 8 log CFU mL −1 (OD 600 ≈0.8) and diluted with fresh sterile LB medium (1:100), then added 1 mL of dilution culture to 24-well polystyrene microtiter plates.…”
Section: Formation and Quantification Of Biofilmsmentioning
confidence: 99%
“…Similarly, various Pseudomonas spp. readily form biofilms under the chilled conditions, such as P. fragi in chilled meat (Wickramasinghe et al, 2019), P. lundensis in pork meat (Liu et al, 2015), and P. fluorescens in fish (Zhu et al, 2019). Moreover, PL were here found to clearly dominate in the co-culture biofilm communities during the incubation period, rather than planktonic state.…”
Section: Discussionmentioning
confidence: 73%
“…Chandler et al (11) reported that AHL is indispensable for inter-species competition. Zhu et al (114) found that there are competitive interactions between Pseudomonas fluorescens and Shewanella baltica, and S. baltica may inhibit the production of AHL in dual-species biofilms or consume the AHL secreted by P. fluorescens. de Almeida et al (16) revealed that Salmonella Enteritidis can form stronger biofilms in the presence of AHL from other species.…”
Section: Qs Signal Moleculesmentioning
confidence: 99%